Feminist Theology and Christian Ministry - John Stephanus Klaasen (African Journal of Gender and Religion (AJGR))
Christian ministry in Catholic, traditional Protestant and Anglican churches is based on the hierarchical and patriarchal ecclesiastical models that separate male and female. Such division gives rise to antagonisms and dualisms which inform the ministry of the church. The question that this article is concerned with is the kind of ministerial model that can be effectively appropriated in the twenty first century Church. Another question flows out of the primary one and has to do with the application of the dialectical approach to Christian ministry by Ruether. I will trace the contrasts in Christian history and then describe the responses of feminist theology within three paradigms. The dialectic approach of Ruether will be applied to two contrasts in order to discover some markers for a model of ministry that is mutually enriching, reciprocal and socially relevant.